Social Media and Self-Perception - Pallavi Dubey (International Journal of Scientific Research in Humanities and Social Sciences, 2025)
Social media platforms have revolutionised the way individuals present and perceive themselves. This study examined the relationship between social media usage and self-perception among young adults. Employing a mixed-methods approach, we surveyed 500 participants using standardised scales and conducted in-depth interviews with a subset of 30 individuals. The results indicate that higher engagement with image‐focused platforms correlates with increased social comparison and lower body satisfaction. Qualitative analyses revealed coping strategies such as selective self‐presentation and digital detox. The implications for mental health interventions and platform design are discussed, along with suggestions for future research.